(untitled) (Revista Brasileira de Contabilidade e Gestão, 2012)
Based on Norma Brasileira de Contabilidade Técnica, NBC T 15, which regulates the disclosure of Environmental and Social informations of enterprises, aimed with the present study to verify whether there are differences in environmental disclosure recommended by NBC T 15 in the year companies exposed profit (2009) for the year that suffered prejudice (2010). The universe of research included the 1000 largest companies in sales, ranked by Revista Exame in its 2011 edition of Melhores e Maiores companies of 2010 published by Exame. The research sample was comprised of 16 companies within the group surveyed, who were among the 20 biggest losses in 2010 in contrast to income recorded in the previous year. For the categorization of evidenced information by the companies, it was noted that the total score generated based on the standard remained practically the same in two years, causing a compensatory oscillation caused by the fact that some firms to increase their disclosure and other cut. The fact that half the companies have not changed their disclosure is consistent with previous studies that don’t consider the result as a determining factor in the level of disclosure. According classification from the amount of information highlighted, most companies remained in the lower categories because of the low information presented.